IMPLEMENTASI PERATURAN DAERAH KOTA BALIKPAPAN NOMOR 8 TAHUN 2012 TENTANG PEMBENTUKAN KECAMATAN BALIKPAPAN KOTA DALAM WILAYAH KOTA BALIKPAPAN - Ardian Nugraha Putra; Anthonius Margono; Bambang Irawan (Jurnal Administrative Reform, 2017)
This research aims to describe, analyse, and interpret the establishment  of Balikpapan Kota district in Balikpapan. This research uses qualitative approach aiming to explore descriptions and deep understanding about  the establishment of Balikpapan Kota district. The data are obtained through interview and as well as documentation, which are then analyzed through data reduction, data presentation, and interpretation of author as well as the drawing of conclusion.